Improving the data recovery for short length LT codes - Nadhir Ibrahim Abdulkhaleq; Faeza Abbas Abed; Ihsan Jabbar Hasan; Falah Hasan Mahdi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Luby Transform (LT) code is considered as an efficient erasure fountain code. The construction of the coded symbols is based on the formation of the degree distribution which played a significant role in ensuring a smooth decoding process. In this paper, we propose a new encoding scheme for LT code generation. This encoding presents a deterministic degree generation (DDG) with time hoping pattern which found to be suitable for the case of short data length where the well-known Robust Soliton Distribution (RSD) witnessed a severe performance degradation. It is shown via computer simulations that the proposed (DDG) has the lowest records for unrecovered data packets when compared to that using random degree distribution like RSD and non-uniform data selection (NUDS). The success interpreted in decreasing the overhead required for data recovery to the order of 25% for a data length of 32 packets.